Spatial planning of the Bueno Brandão (MG) municipality with emphasis on hydrographic sub-basins - Débora Paula Simões; Angelo Marcos Santos Oliveira (Revista Agrogeoambiental, 2024)
Territorial planning must be carried out with the objective of organizing human activities so to promote sustainable development, reconciling human well-being with environmental preservation. In this context, this study was developed with an initial proposal for the spatial planning of the municipality of Bueno Brandão (MG), using the hydrographic sub-basins as environmental planning units. For this purpose, the Geographic Information System software QGIS was used to structure a database composed of hydrographic, altimetric information, municipal limits and spatial distribution of rural clusters and the urban area of the municipality. The Digital Elevation Model, obtained from the Shuttle Radar Topography Mission project, was also used. Google Earth images were used to verify that the areas of population concentration coincided with the limits of the sub-basins. The initial proposal for Bueno Brandão spatial planning resulted in the identification of 43 rural clusters and the delimitation of the urban area, distributed in 12 hydrographic sub-basins.